Breast Cancer Conditioned Media Modulate the Expression of Immune Checkpoints and Adhesion Molecules in Endothelial Cells - İpek Türkdönmez; Emel Şahin; Mehmet Şahin (Turkish Journal of Immunology)
Objective: Breast cancer is commonly originated from the cells in the milk ducts or in the lobules that supply milk to the ducts. During cancer development, many actors, including cellular factors such as endothelial and immune cells, and structural factors such as integrins and extracellular matrix elements have gained importance in the tumor microenvironment. Endothelial cells (ECs) not only implicate in cancer growth and metastasis processes, but also are effective in immune cells' modulations. In the present study, we investigated the effect of secretome released by breast carcinoma cell lines on endothelial expression of immune checkpoints and adhesion molecules. Materials and Methods: In this study, the expression levels of some immune checkpoints, including lymphocyte-activation-protein 3 (LAG-3), V-domain Ig suppressor of T-cell activation (VISTA), Indoleamine-2,3-dioxygenase (IDO), IDO-2, programmed cell death 1 ligand (PD-L1), PD-L2, Cytotoxic T-lymphocyte associated protein 4, (CTLA-4), and some adhesion molecules, including E-cadherin, VE-cadherin, E-selectin, platelet EC adhesion molecule-1 (PECAM-1), vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), were measured using quantitative real-time polymerase chain reaction in HUVEC ECs preincubated with the conditioned media (CM) collected from normal (CRL-4010) and carcinoma cells (CRL-2329 and MDA-MB-231). Besides, endothelial proliferation and migration were also examined. Results: CRL-2329-CM was found to increase cell proliferation at the end of 48 h but not 24 h, compared to the control (CRL-4010-CM) group (p=0.0052). In addition, both cancer cell-CMs were revealed to induce migration (p<0.001). VE-cadherin, ICAM-1, PECAM-1, VCAM-1, and E-selectin gene expressions were found to be increased significantly in the 48 h groups (p<0.001). The expression levels of PD-L1 (p=0.0028 and p<0.001), PD-L2 (p=0.0216 and p<0.001), IDO-1 (p<0.001), LAG3 (p<0.001 only for MDA-MB CM group), VISTA (p<0.001) genes in 48 h groups, and PD-L2 (p=0.0084 and p=0.0045) gene in 24 h groups, were significantly increased. However, we found that there were no expressions of IDO-2, CTLA-4 and E-cadherin genes in ECs. Conclusion: This study has shown that secretome produced by breast carcinoma cell lines may promote endothelial proliferation and migration and support metastasis. Also, secretome can be effective on immune modulation.